Contribuições para o aprimoramento da administração tributária dos municípios do Espírito Santo - Westphal, João Henrique Rodrigues (2021)
Most municipalities in espírito santo have not been able to meet the limits of personnel expenditure defined by the Fiscal Responsibility Law (LRF), which entails a series of restrictive measures to the person, compromising the final objective of the Democratic State of Law, that is, to meet the demands of society. Then arises the problem, which would be what improvements can be proposed to contribute to the improvement of the tax administration of the municipalities of Espírito Santo. Considering that the theme is directly of interest to society, as well as the low focus that has been given in relation to the municipalities, in this context, this study has as justification to present an improvement in the fiscal management of municipalities with a view to increasing the sources of own revenue collection, to the extent that it is observed that most municipalities in the State of Espírito Santo remain the basis of external resources , derived from constitutionally provided for transfers. Thus, the main objective is to suggest improvements in the municipal own collection in order to minimize the problem and provide better financial conditions for these entities to meet the demand of their population. In theoretical terms, scientific articles, periodicals, books and documents were used to support the arguments in the present study. Regarding the methods and procedures, the qualitative dimension was used, configuring the research as of an applied nature. Data were collected in bibliography of the area of management and public finances, as well as government websites. Following this line, we obtained, at the end, enough elements to define a path with the purpose of possible solutions to the problem faced, reaching a technological product of an applied nature that can contribute to a qualified public management.